Women’s activism and women’s writing – survival strategies in the novel Ravnoteža [Balance] and journal ProFemina of the author and editor Svetlana Slapšak (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper will carry out a comparative analysis of the textual politics in the novel Ravnoteža [Balance] and the anthropological essays of Svetlana Slapšak, which the author published as independent publications or as the editorial in the feminist and anti-war journal from the nineties – ProFemina. The aim of this analysis is to examine how opposed ideological paradigms – the feminist and the nationalist one – are reflected in the field of literary production. That is, paper wishes to show how the poetics of the novel, published more than two decades after ProFemina was started as one of the newsletters of the feminist and peaceful counterpublic, corresponds with Slapšak’s editorial politics. That editorial politics rested on the belief that activism, theory and literary texts are connected by discursive strategies which affirm or negate the socio-political context. Therefore, to understand key places in the novel Ravnoteža, it was necessary to take feminist ideas presented in ProFemina into consideration; ideas which were an indispensable part of the resistance strategy against the repressive and nationalist regime of the 90s.
Keywords: textual politics; ProFemina; feminist counterpublic; women’s writing